2023
DOI: 10.1161/strokeaha.122.040823
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Onset and Progression of Cerebral Amyloid Angiopathy

Abstract: Background: Cerebral Amyloid Angiopathy (CAA) disease course is highly variable even in hereditary forms. Sex may be a possible modifying factor. We investigated biological sex differences in clinical disease course and magnetic resonance imaging-markers in sporadic (sCAA) and Dutch-type hereditary CAA (D-CAA). Methods: Patients with D-CAA and sCAA were included from hospital and research databases of the Leiden University Medical Center (2012–2020) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 35 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Sex may also play a key role in CAA progression. A study of patients with HCHWA-D and sCAA found that male sex and sCAA may be related to an earlier onset and longer course of CAA [ 12 ].…”
Section: Etiology and Epidemiology Of Caamentioning
confidence: 99%
“…Sex may also play a key role in CAA progression. A study of patients with HCHWA-D and sCAA found that male sex and sCAA may be related to an earlier onset and longer course of CAA [ 12 ].…”
Section: Etiology and Epidemiology Of Caamentioning
confidence: 99%
“…We also found an independent association between female sex and the presence of non‐hemorrhagic CAA markers. Although in some population‐based studies, 37 cohorts of patients with CAA, 40 and memory clinic cohorts, 41 no association between sex and CSO‐EPVS burden was found, other studies have found an increased CSO‐EPVS burden in women with CAA 42 and a higher age‐related rate of increased EPVS in women 43 . Very little was found in the literature on the question of sex differences and the presence of the multispot pattern.…”
Section: Discussionmentioning
confidence: 99%
“…), our results showing sex differences in migratory responses to injury could have functional implications. Human studies are rather mixed but show that males diagnosed with cerebral amyloid angiopathy ( 87 ), mild cognitive impairment, or Alzheimer disease ( 88 ), have significantly more cerebral microbleeds than females ( 89 ), whereas females with small vessel disease have increased microbleed burden ( 90 ). In rodents, the picture appears more consistent where female mice exhibit more abundant microbleeds than males in mouse models of Alzheimer disease ( 91 ) or cerebral amyloid angiopathy ( 92 ).…”
Section: Discussionmentioning
confidence: 99%